Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands - Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Naeemi, E.; Ratner, B.D. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2009)
This study focuses on the selective binding of albumin to a nanostructured surfaces to inhibit other blood proteins from adsorbing thereby reducing platelet adhesion and activation. Tetra (ethylene-glycol)-terminated self- assembled monolayers (EG4 SAMs) with different percentages of CI 8 ligands on the surface were characterized by contact angle measurements, X-ray photoelectron microscopy, infrared reflection-absorption spectroscopy, and ellipsometry. A specific surface (2.5% C18 SAM) was found to be selective for human serum albumin (HSA) in the presence of both albumin and fibrinogen (HFG). The importance of this concentration of C18 ligands was stressed in reversibility studies since that surface exchanged almost all the preadsorbed HSA by HSA in solution, but not by HFG. The effect of protein adsorption in the subsequent adhesion and activation of platelets was studied by pre-immersing the surfaces in albumin and plasma before contact with platelets. Scanning electron microscopy and glutaraldehyde induced fluorescence technique images showed that as surfaces got more hydrophobic due to the immobilization of C18 ligands, the number of adherent platelets increased and their morphology changed from round to fully spread. Pre-immersion in HSA led to an 80°/o decrease in platelet adhesion and reduction of activation. Pre-immersion in 1% plasma was only relevant in 2.5% CI 8 SAMs since this was the only surface that demonstrated less adhesion of platelets comparing with buffer pre-immersion. However, they still adsorb more platelets then when HSA was preadsorbed. This was confirmed in competition studies between HSA and plasma that suggested that other plasma proteins were also adsorbing to this surface. © 2008 Wiley Periodicals, Inc.
Cited By (since 1996): 11Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32011PubMed ID: 18442116Language of Original Document: EnglishCorrespondence Address: Gonçalves, I. C.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Universidade do Porto, Run do Campo Alegre, 823, 4150-180 Porto, Portugal; email: icastro@ineb.up.ptChemicals/CAS: fibrinogen, 9001-32-5; glutaraldehyde, 111-30-8, 37245-61-7; human serum albumin, 9048-49-1; Carbon, 7440-44-0; Ethylene Glycol, 107-21-1; Ligands; Serum AlbuminReferences: Nath, N., Hyun, J., Ma, H., Chilkoti, A., Surface engineering strategies for control of protein and cell interactions (2004) Surf Sci, 570, pp. 98-110;Mao, C., Qiu, Y.Z., Sang, H.B., Mei, H., Zhu, A.P., Shen, J., Lin, S.C., Various approaches to modify biomaterial surfaces for improving hemocompatibility (2004) Adv Colloid Interface Sci, 110, pp. 5-17; Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: Roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25, pp. 5681-5703; Kottkemarchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the in vitro blood compatibility of dacron arterial prostheses (1989) Biomaterials, 10, pp. 147-155; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Trans Am Soc Artif Intern Organs, 27, pp. 499-503; Eberhart, R.C., Munro, M.S., Williams, G.B., Kulkarni, P.V., Shannon, W.A., Brink, B.E., Fry, W.J., Albumin adsorption and retention on C-18-alkyl-derivatized polyurethane vascular grafts (1987) Artif Organs, 11, pp. 375-382; Frautschi, J.R., Munro, M.S., Lloyd, D.R., Eberhart, R.C., Alkyl derivatized cellulose-acetate membranes with enhanced albumin affinity (1983) Trans Am Soc Artif Intern Organs, 29, pp. 242-244; Pitt WG, Cooper SL. Albumin adsorption on alkyl chain derivatized polyurethanes. I. The effect of C-18 alkylation. T Biomed Mater Res 1988;22:359-382Johnston, E., Ratner, B.D., Protein Adsorption: Friend or Foe? (1998) Immobilized biomolecules in analysis: A practical approach, pp. 79-94. , Cass T, Ligler FS, editors, Oxford: Oxford University Press;; Ji, J., Feng, L.X., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin (2001) Biomaterials, 22, pp. 3015-3023; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on cibacron blue F3G-A immobilized onto oligo (ethylene glycol)-terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14, pp. 945-954; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) J Am Chem Soc, 120, pp. 3464-3473; Palegrosdemange, C., Simon, E.S., Prime, K.L., Whitesides, G.M., Formation of self-assembled monolayers by chemisorption of derivatives of oligo(ethylene glycol) of structure Hs(Ch2)11 (Och2ch2)meta-Oh on gold (1991) J Am Chem Soc, 113, pp. 12-20; Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-ter- minated self-assembled monolayers (2005) Biomaterials, 26, pp. 3891-3899; Martins MCL, Ratner BD, Barbosa MA. Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolavers. I Biomed Mater Res 2003;67A: 158-171Owens, D.K., Wendt, R.C., Estimation of surface free energy of polymers (1969) J Appl Polym Sci, 13, pp. 1741-1747; Sousa, S.R., Moradas Ferreira, P., Saramago, B., Viseu Melo, L., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Sastry, M., A note on the use of ellipsometry for studying the kinetics of formation of self-assembled monolayers (2000) Bull Mater Sci, 23, pp. 159-163; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ralner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Frank, R.D., Dresbach, H., Thelen, H., Sieberth, H.G., Glutardialde- hyde induced fluorescence technique (GIFT): A new method for the imaging of platelet adhesion on biomaterials (2000) J Biomed Mater Res, 52, pp. 374-381; Herrwerth, S., Eck, W., Reinhardt, S., Grunze, M., Factors that determine the protein resistance of oligoether self-assembled monolayers-internal hydrophilicity, terminal hydrophilicity, and lateral packing density (2003) J Am Chem Soc, 125, pp. 9359-9366; Harder, P., Grunze, M., Dahint, R., Whitesides, G.M., Laibinis, P.E., Molecular conformation in oligo(ethylene glycol)-terminated self-assembled monolayers on gold and silver surfaces deter-mines their ability to resist protein adsorption (1998) J Phys Chem B, 102, pp. 426-436; Schwendel, D., Dahint, R., Herrwerth, S., Schloerholz, M., Eck, W., Grunze, M., Temperature dependence of the protein resistance of poly- and oligo(ethylene glycol)-terminated alkanethiolate monolayers (2001) Langmuir, 17, pp. 5717-5720; Zhu, B., Eurell, T., Gunawan, R., Leckband, D., Chain-length dependence of the protein and cell resistance of oligo(ethylene glycol)-terminated self-assembled monolayers on gold (2001) J Biomed Mater Res, 56, pp. 406-416; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (1999) J Biomed Mater Res, 49, pp. 435-447; Sperling, C., Schweiss, R.B., Streller, U., Werner, C., In vitro hemocompatibility of self-assembled monolayers displaying various functional groups (2005) Biomaterials, 26, pp. 6547-6557; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethio- lates on gold (2004) Biomaterials, 25, pp. 2557-2563
Keywords: Absorption spectroscopy; Acoustic microscopes; Adhesion; Adsorption; Albumin; Aldehydes; Angle measurement; article; Biological materials; Biomaterials; Blood Platelets; Blood protein; Blood substitutes; Carbon; Cell Shape; chemical composition; Concentration of; Contact angle; controlled study; Ethylene; Ethylene Glycol; ethylene glycol derivative; fibrinogen; Fluorescence technique; glutaraldehyde; gold nanoparticle; human; human serum albumin; Human serum albumins; Humans; hydrophobicity; Infrared reflection absorption spectroscopy; infrared spectroscopy; ligand; Ligands; Nanostructured surface; normal human; Oligo(ethylene glycol); Photoelectron spectroscopy; plasma; Plasma diagnostics; Plasma protein; Plasmas; Platelet adhesion; Platelet Adhesiveness; Platelets; Protein adsorption; protein binding; Proteins; Sams; Scanning electron microscopy; Selective binding; Selective protein adsorption; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; Serum Albumin; Specific surface; Spectrophotometry, Infrared; Surface Properties; surface property; thrombocyte activation; thrombocyte adhesion; thrombocyte shape; X ray photoelectron spectroscopy; X-ray photoelectron microscopy

Albumin adsorption on Cibacron Blue F3G-A immobilized onto oligo(ethylene glycol)-terminated self-assembled monolayers - Martins, Ma.C.L.; Naeemi, E.; Ratner, B.D.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2003)
Self-assembled monolayers can be tailored with specific ligands to a certain protein and at the same time prevent the non-specific adsorption of other proteins. Cibacron Blue F3G-A (CB-thiol) was successfully immobilized onto tetra(ethylene glycol)-terminated alkanethiol (CB-thiol). The affinity of human serum albumin (HSA) to immobilized Cibacron Blue F3G-A was studied using mixed thiolate self-assembled monolayers on gold with different n-alkyl chain lengths and functional terminal groups (CH 3-; OH- and tetra(ethylene glycol)). Surfaces were characterized using X-ray photoelectron spectroscopy and water contact angle measurements. Albumin adsorption and exchangeability of the adsorbed albumin molecules with other albumin molecules in solution were evaluated using 125I-radiolabeled HSA. Competitive adsorption between albumin and fibrinogen to the different self-assembled monolayers (SAMs) was also investigated. Results showed that the incorporation of CB-thiol on the monolayers does not increase the HSA adsorption and reversibility on the SAMs. However, although specific adsorption of HSA to the immobilized Cibacron Blue F3G-A was not demonstrated, the presence of CB-thiol decreases the affinity of fibrinogen to the OH-terminated SAMs. © 2003 Kluwer Academic Publishers.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1026394431100Language of Original Document: EnglishCorrespondence Address: Martins, Ma.C.L.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: cibacron blue f3ga, 12236-82-7, 53127-08-5; ethylene glycol, 107-21-1; fibrinogen, 9001-32-5; gold, 7440-57-5; human serum albumin, 9048-49-1; iodine 125, 14158-31-7, 22822-81-7; macrogol, 25322-68-3; thiol derivative, 13940-21-1; water, 7732-18-5References: Ratner, B.D., (1996) J. Mol. Recognit., 9, p. 617;Kottke-Marchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., (1998) Biomaterials, 10, p. 147; Dequeiroz, A.A.A., Barrak, E.R., Gil, H.A.C., Higa, O.Z., (1997) J. Biomater. Sci. Polym. Ed., 8, p. 667; Kamath, K.R., Park, K., (1994) J. Appl. Biomater., 5, p. 163; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., (1981) Trans. Am. Soc. Artif. Intern. Organs, 27, p. 499; Ji, J., Feng, L., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Keogh, J.R., Eaton, J.W., (1994) J. Lab. Clin. Med., 121, p. 537; Wang, D., Chen, B., Ji, J., Feng, L., (2002) Bioconjugate Chem., 13, p. 792; Ji, J., Barbosa, M.A., Feng, L., Shen, J., (2002) J. Mat. Sci. Mat. Med., 13, p. 677; Mcfarland, C.D., Jenkins, M., Griesser, H.J., Chatelier, R.C., Steele, J.G., Underwood, P.A., (1998) J. Biomater. Sci. Polym. Ed., 9, p. 1207; Mcfarland, C.D., Filippis, C.D., Jenkins, M., Tunstell, A., Rhodes, N.P., Williams, D.F., Steele, J.G., (1998) J. Biomater. Sci. Polym. Ed., 9, p. 1277; Kopperschlager, G., Bohme, H.J., Hofmann, E., (1982) Adv. Biochem. Eng., 25, p. 101; Travis, J., Bowen, J., Tewksbury, D., Johnson, D., Pannell, R., (1976) Biochem. J., 157, p. 301; Leatherbarrow, R.L., Dean, P.D.G., (1980) Biochem. J., 189, p. 27; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., (2003) J. Biomater. Sci. Polym. Ed., 14, p. 439; Dockal, M., Carter, D.C., Ruker, F., (1999) J. Biol. Chem., 274, p. 29303; Ostuni, E., Yan, L., Whitesides, G.M., (1999) Colloid Surf. B-Biointerfaces, 15, p. 3; Ulman, A., (1991) An Introduction to Ultrathin Organic Films: From Langmuir-Blodgett to Self-Assembled, , Academic Press Inc: San Diego, CA, USA; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., (1989) J. Am. Chem. Soc., 111, p. 321; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., (1987) J. Am. Chem. Soc., 109, p. 3559; Sigal, G.B., Mrksich, M., Whitesides, G.M., (1998) J. Am. Chem. Soc., 120, p. 3464; Seigal, R.R., Harder, P., Dahint, R., Grunze, M., (1997) Anal. Chem., 69, p. 3321; López, G.P., Biebuyck, H.A., Harter, R., Kumar, A., Whitesides, G.M., (1993) J. Am. Chem. Soc., 115, p. 10774; Prime, K., Whitesides, G.M., (1991) Science, 252, p. 1164; Chinn, J.A., Horbett, T.A., Ratner, B.D., (1991) Thromb. Haemost., 65, p. 608; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Silva, M.F., (1999) IEEE Trans. Magn., 35, p. 4361; Pale-Grosdemange, C., Simon, E.S., Prime, K.L., Whitesides, G.M., (1991) J. Am. Chem. Soc., 113, p. 12; Castner, D.G., Hinds, K., Grainger, D.W., (1996) Langmuir, 12, p. 5083; Lin, J.C., Chuang, W.H., (2000) J. Biomed. Mater. Res., 51, p. 413; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, p. 45; (1993) Iodine-125, a Guide to Radioiodination Techniques - Amersham Life Science, p. 64. , Amersham International plc, Amersham Place, Little Chalfont, Bucks. HP7 9NA, England; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of Biocompatibility Tests, p. 183. , edited by D. F. Williams (Harcover, CRC Pr); Du, Y.J., Cornelius, R.M., Brash, J.L., (2000) Colloid Surf. B-Biointerfaces, 17, p. 59; Beamson, G., Briggs, D., (1992) High Resolution XPS of Organic Polymers - The Scienta ESCA300 Database, , John Wiley & Sons Ltd, Chichester, England; htpp://www.lasurface.com/Tarlov, M.J., Burgess Jr., D.R.F., Gillen, G., (1993) J. Am. Chem. Soc., 115, p. 5305; Tegoulia, V.A., Cooper, S.L., (2000) J. Biom. Mater. Res., 50, p. 291; Ishida, T., Tsuneda, S., Nishida, N., Hara, M., Sasabe, H., Knoll, W., (1997) Langmuir, 13, p. 4638; Silver, J.H., Hergenrother, R.W., Lin, J.C., Lim, F., Lin, H.B., Okada, T., Chaudhury, M.K., Cooper, S.L., (1995) J. Biom. Mater. Res., 29, p. 535; Smith, T., (1980) J. Colloid. Interf. Sci., 75, p. 51; Tidwell, C.D., Ertel, S.I., Ratner, B.D., (1997) Langmuir, 13, p. 3404; Silin, V., Weetall, H., Vanderah, D., (1997) J. Colloid. Interf. Sci., 185, p. 94; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., (2003) J. Biom. Mater. Res., 67 A, p. 158; Schlereth, D.D., (1997) Sens. Actuator B-Chem., 43, p. 78; Mrksich, M., Grunwell, J.R., Whitesides, G.M., (1995) J. Am. Chem. Soc., 117, p. 12009; Hodneland, C.D., Lee, Y.S., Min, D.H., Mrksich, M., (2002) PNAS, 99, p. 5048; Malmsten, M., Lassen, B., (1994) J. Colloid. Interf. Sci., 166, p. 490; Feng, L., Andrade, J.D., (1994) Biomaterials, 15, p. 323; Bertilsson, L., Butt, H.J., Nelles, G., Schlereth, D.D., (1997) Biosens. Bioelectron., 12, p. 839
Keywords: Adsorption; Albumin; aqueous solution; article; Cell immobilization; cibacron blue f3ga; Contact angle; controlled study; Drug products; Ethylene Glycol; fibrinogen; functional group; Glycols; gold; human; human serum albumin; iodine 125; isotope labeling; ligand; macrogol; molecule; priority journal; protein assembly; protein binding; protein immobilization; protein structure; Proteins; radioassay; Self assembly; surface property; synthesis; tetra(ethylene glycol) undecanethiol; thiol; thiol derivative; unclassified drug; Water; X ray photoelectron spectroscopy